Classifying and planning BPR initiatives: the BPR web - Edwards, Chris; Braganza, Ashley (Cranfield University, 1994)
The purpose of this paper is to propose a framework for classifying Business Process Redesign (BPR) initiatives, and to share its initial application in organisations undertaking BPR. There is a growing necessity for such a framework as BPR is being reduced to a cliche, which today includes almost any change initiative. Such a generalising of BPR would be a great pity as it effectively debars one organisation from learning from the experience of others. Possibly the most significant benefit from the framework is that it will provide a language to facilitate communication between organisations to share experiences of BPR. Additionally the Web is a management tool as it facilitates selection of appropriate management styles for various classes of BPR. Research work at Cranfield continues to expand experiences of usage of the Web. However, even at this stage it is proving a useful framework to which practising managers are able to relate.